Co-Amorphous Solid Dispersions: A Strategy for Improving Poorly Soluble Drug Delivery using Amino Acids and Hydrophilic Carriers (Asian Journal of Pharmaceutics (AJP), 2025)
Class II drugs in the Biopharmaceutical Classification System (BCS) are characterized by low solubility andhigh permeability, necessitating enhanced dissolution to improve their bioavailability and therapeutic efficacy.This review focuses on solid dispersion (SD) strategies, particularly using amino acids (AAs), to enhance theaqueous solubility of compounds, including hydrogen bonding, ionic interactions, and π–π stacking. The reviewalso outlines various techniques for preparing amorphous SDs, such as hot melt extrusion, spray drying, andsolvent evaporation, highlighting their scalability and feasibility for pharmaceutical manufacturing. Due to theirunique physicochemical properties, AAs serve as effective co-formers in SDs, contributing to the stabilization ofthe amorphous state and preventing drug recrystallization, a significant limitation in conventional approaches.Finally, the review discusses strategies to overcome key challenges associated with SD and concludes thatAA-based systems offer a promising avenue for enhancing the solubility and bioavailability of BCS class II drugs,potentially leading to improved clinical efficacy and patient outcomes.